2021
DOI: 10.15537/smj.2021.42.7.20200582
|View full text |Cite
|
Sign up to set email alerts
|

HspX-mediated survival pathways of pathogenic mycobacteria

Abstract: We first optimized ELISA conditions for the detection of HspX. The optimization protocol focused on minimizing concentrations of the capture Original Article antibody, detection antibody, and conjugated secondary antibody, and determining the minimum detection limit of the antigen, HspX. Bacteria were grown either in shaking culture or in stationary flasks mimicking hypoxic environments. A standard Bradford assay was used to determine the total protein and HspX was detected using the optimized ELISA protocol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In addition, Hu et al [ 41 ] found that GroEL2 is an essential protein for the growth of Mtb. HspX is the major antigen during the latent infection phase of Mtb and is involved in mycobacterial survival as a potent molecular chaperone that protects proteins from aggregation in vitro and serves as an antigen for the rapid diagnosis of Mtb [ 42 44 ]. The greater antigenicity of the DnaK protein can stimulate T cells to generate an immune response, which is valuable for the diagnosis of TB and the research of novel anti-TB vaccines [ 45 ], and it has been shown that overexpression of DnaK in Mtb enhances the clearance of pathogens in a mouse model [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hu et al [ 41 ] found that GroEL2 is an essential protein for the growth of Mtb. HspX is the major antigen during the latent infection phase of Mtb and is involved in mycobacterial survival as a potent molecular chaperone that protects proteins from aggregation in vitro and serves as an antigen for the rapid diagnosis of Mtb [ 42 44 ]. The greater antigenicity of the DnaK protein can stimulate T cells to generate an immune response, which is valuable for the diagnosis of TB and the research of novel anti-TB vaccines [ 45 ], and it has been shown that overexpression of DnaK in Mtb enhances the clearance of pathogens in a mouse model [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…hspX and tgs1 are genes in the DosR regulatory system, which play a role in mycobacterial persistence and are essential for modulating cellular metabolism upon entry into and during dormancy [13,56]. hspX and tgs1 are regulated in hypoxia, multiple-stress model, macrophage infection, and dormancy [12,[57][58][59][60]. However, the role of the DosR regulatory system in virulence is model dependent [61].…”
Section: Discussionmentioning
confidence: 99%